In pursuit of great and godly leadership : tapping the wisdom of the world for the kingdom of God - Bonem, Mike, 1959- (San Francisco : Jossey-Bass, 2012)
"A guide for applying the best of business insight for church leadership In Pursuit of Great AND Godly Leadership explores the issues involved in bringing secular leadership knowledge into the world of church leadership. Most church leaders in large churches are entrepreneurial, well-educated, and keenly aware of the general leadership literature, but they don't always know the best ways to apply those insights in leading their churches. In this new book, church consultant and pastor Mike Bonem explores how leaders can discern the value of business practices and allow time and space for God to speak to their hearts. Explores how church leaders can use strategic planning and other business skills to further their mission Written by an expert in congregational leadership, Mike Bonem has an MBA from Harvard Business School Helps leaders think more productively about issues such as financial management, strategic planning, systems thinking, growth with a combination of business acumen and spiritual wisdom Bonem shows church leaders exactly how to make, evaluate, and use secular knowledge"--
Is great the enemy of godly? -- Where should you begin? -- Is God in your plans? -- Are your plans fruitful? -- Who is on the bus? -- Do you measure what matters? How will you finance the dream? -- Are "all systems go"? -- Is everyone on the same page? -- Why is culture important? -- Are you guarding your heart?
Includes bibliographical references (p. 249-252) and index.
Keywords: Christian leadership; Leadership -- Religious aspects -- Christianity; Leadership